Plant nutrient contribution by rainfall in the highly industrialized and polluted Patancheru area in Andhra Pradesh - Murthy, K.V.S.; Sahrawat, K.L.; Pardhasaradhi, G. (2000)
Rainwater contains nutrients and can, in a low-input situation, constitute an important nutrient source for crop production. During 1981–90, rainwater was collected using standardized collection procedures at three different locations at ICRISAT, Patancheru, Andhra Pradesh. Samples were analysed for N, P, K, S, Ca, Mg and Na. Ion concentrations were low and varied from year to year. The mean pH was 7.05. Because the locations were close to each other, there was no significant. variation in the composition of rainwater among the locations. There were negative correlations between the amount of rainfall and the chemical parameters. Phosphorus was positively correlated with N, K, S, Ca, Mg and Na. Patancheru is highly industrialized and its atmosphere will have a bearing on the composition of rainwater. Sulphur fertilizer response experiments should not be carried out at this location. On an average, rainfall at this location contributes, per hectare, 5.8 kg N, 0.4 kg P, 4.8 kg S, 1.7 kg Ca, 1.7 kg Mg and 10.5 kg Na. The increase in N, P and S contribution was higher during 1986–90 than in 1981–85.